2016
DOI: 10.17116/flebo2016104199-213
|View full text |Cite
|
Sign up to set email alerts
|

The Genetic Base of Chronic Venous Disease: a Review of Modern Concepts

Abstract: Хронические заболевания вен (ХЗВ) нижних ко-нечностей представляют собой одно из наиболее часто встречающихся заболеваний сосудистой системы. Оценки распространенности варикозного расширения вен (ВРВ) варьируют в широких пределах: от 2 до 56% у мужчин и от 1 до 73% у женщин [1]. Различия в распро-страненности могут быть объяснены рядом факторов, в том числе методологией исследований. В целом, рас-пространенность выше в более развитых индустриаль-ных странах, чем в слаборазвитых регионах. 3 «новосибирский нацио… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 68 publications
(73 reference statements)
0
1
0
Order By: Relevance
“…Subsequently, inheritance patterns and the results of family and twin studies were examined in 2003 by the French scientist Pistorius [10] , who hypothesized about the possible genetic heterogeneity of VVD, suggesting the existence of different genotypic profiles with a similar phenotype. Many studies by other scientists have also shown a significant genetic contribution to the etiology of VVD, as reported in a review by the New Zealand group of Krysa et al [11] . Since then, genetic research has continued and gained strength and momentum.…”
Section: Hereditary Constituent Of Varicose Vein Pathogenesis-an Overviewmentioning
confidence: 83%
“…Subsequently, inheritance patterns and the results of family and twin studies were examined in 2003 by the French scientist Pistorius [10] , who hypothesized about the possible genetic heterogeneity of VVD, suggesting the existence of different genotypic profiles with a similar phenotype. Many studies by other scientists have also shown a significant genetic contribution to the etiology of VVD, as reported in a review by the New Zealand group of Krysa et al [11] . Since then, genetic research has continued and gained strength and momentum.…”
Section: Hereditary Constituent Of Varicose Vein Pathogenesis-an Overviewmentioning
confidence: 83%